DETERMINANTS OF HYPERTENSION OCCURRENCE - Wahyudi, Gufron; Hijriyati, Yoanita (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Hypertension stands as a primary peril for cardiovascular ailments, potentially culminating in fatalities by inducing complications like heart disease, stroke, and kidney issues. This study scrutinizes the prevalence and risk factors associated with hypertension at Puskesmas Kedungrejo Muncar, Banyuwangi, spotlighting age and body mass index (BMI) as pivotal predictors. Employing a descriptive analytic method with a cross-sectional design, data was gathered through purposive sampling from 64 individuals. Findings unveil a significant correlation between advancing age and hypertension, aligning with previous research attributing this link to deteriorating cardiovascular function and arterial stiffness. Meanwhile, gender and educational attainment emerged as non-significant predictors, contrasting with the notable influence of BMI, with hypertensive individuals often exhibiting a normal BMI. These results accentuate the necessity of comprehending modifiable risk factors like BMI and emphasize the requisite for targeted interventions to combat hypertension in the community. Prevention and management endeavors ought to prioritize age-related considerations and initiatives aimed at fostering healthy BMI levels.